BRCA1 and BRCA2: Lack of Certainty and Its Clinical Implications - Samuel J Haryono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
AbstractIn this time of amounting cancer incidence and mortality, genetic testing may be greatly valuable in deciding on appropriate clinical management. It is unfortunate that the test is not a practical interrogative problem. When positive, the patients can settle down with what to do next, whereas when negative, their family members may breathe out in relief from unnecessary intensive surveillance and prophylaxis, and then there is VUS (Variants of Uncertain Significance).            How should a health provider deliver the elaboration and implication of VUS to a patient who had expended a lump sum of and had expected a level of certainty? Variants of UncertainSignificance have nowadays become a challenging spoiler in the setting of clinical management of cancer. How would one inform someone else on anything uninformative?            BRCA1 and BRCA2 are two genes with high penetrance in breast cancer. Since their functions as tumor suppressor genes and DNA repair regulators, their mutation effects are only visible when there is Loss of Heterozygosity. Mutation of BRCA1/2 gene can be demonstrated within the tissue specimen and blood sample DNA; that would mean it has occupied all tissues and is inheritable.            In the case of BRCA1 and BRCA2 mutations, 10-20% of all genetic test results will read VUS,  In one previous study of sixteen Indonesian patients, 13 (81,25%) patients had VUS. There were variants that had not been found in other population. Trans-academically speaking, the reclassification of VUS in BRCA1/2 gene is not merely a challenge to clarify its clinical impacts, but also an obligation to accomplish our community contribution to science.There can be a set of factors to suggest that a VUS may be a deleterious mutation:Co-segregation: when the variant comes with multiple and multigenerational incidence of cancer, it is possible.Epidemiology: when a case control study demonstrates prevalence discrepancy, it is possible.Co-occurrence with deleterious mutation: when the variant is shared within the same gene in other individuals, it is possible.Evolutionary data: when the sequence is carried across species, it is possible.Amino acid substitution: when the substitute is structurally similar, it is impossible.Loss of heterozygosity: when there is loss of a wild type allele in tumor specimen, it is possible.Functional analysis: should an in vitro assay demonstrate a loss of protein function, it is probable.The ultimate solution is not yet available. However, there is clinical significance for families with VUSs, only if that can confidently be classified as the presence or absence of the associated disease. That condition may be achieved by increasing the availability of genetic testing so that there can be a larger, open-access repertoire of VUSs.